2013
DOI: 10.1002/oby.20507
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin‐2 increases fat oxidation in vitro and is correlated with energy expenditure in normal weight but not obese women

Abstract: Objective: The role of lipocalin-2 (Lcn2) was determined in regulating metabolism in cell, animal, and human models. Design and Methods: Adipocytes were treated with recombinant lipocalin-2 (rLcn2) to determine the effect on lipid metabolism. rLcn2 was injected into mice to determine the effect on metabolism in vivo. To assess the relationship between Lcn2 and fat oxidation (FatOx) in humans, normal weight (NW) and obese (OB) women were given three separate high fat (HF) meals followed by indirect calorimetry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
(37 reference statements)
7
28
2
Order By: Relevance
“…In agreement with the above observations, in a recent study, total body Lcn2 ‐deficient mice showed hyperphagia, increased body weight and fat mass, along with hyperinsulinaemia, polyuria, glycosuria and fasted hypoglyacemia as compared to wild‐type mice . Several other studies using global Lcn2 deletion mice models imply an amelioration of energy metabolism by LCN2, as LCN2 was reported to protect mice from diet‐induced obesity, fatty liver disease, atherogenic dyslipidaemia and insulin resistance, to suppress hepatic gluconeogenesis, and to promote adaptive thermogenesis, browning of adipose tissue and fatty acid oxidation . Chronic administration of exogenous LCN2 in lean and obese mice decreased food intake, fat mass and body weight gain and improved glucose metabolism and energy expenditure .…”
Section: Osteoblast‐derived Lcn2 As An Appetite Suppressorsupporting
confidence: 76%
“…In agreement with the above observations, in a recent study, total body Lcn2 ‐deficient mice showed hyperphagia, increased body weight and fat mass, along with hyperinsulinaemia, polyuria, glycosuria and fasted hypoglyacemia as compared to wild‐type mice . Several other studies using global Lcn2 deletion mice models imply an amelioration of energy metabolism by LCN2, as LCN2 was reported to protect mice from diet‐induced obesity, fatty liver disease, atherogenic dyslipidaemia and insulin resistance, to suppress hepatic gluconeogenesis, and to promote adaptive thermogenesis, browning of adipose tissue and fatty acid oxidation . Chronic administration of exogenous LCN2 in lean and obese mice decreased food intake, fat mass and body weight gain and improved glucose metabolism and energy expenditure .…”
Section: Osteoblast‐derived Lcn2 As An Appetite Suppressorsupporting
confidence: 76%
“…IL-8 is correlated with insulin resistance in obesity and metabolic syndrome [30,31] while PAI-1 is associated increased visceral fat mass [32] and insulin resistance in lean individuals [33]. Lipocalin-2 is associated with increased total energy expenditure and increased fat oxidation [34], and TNFα induces lipolysis [27]. Therefore, the increased expression of adiponectin, IL-6, IL-8, lipocalin-2, PAI-1 and TNFα that we observe in ALS may contribute to the reported occurrence of glucose intolerance and insulin resistance [26,35], hypermetabolism [12,13] and the loss of fat mass [18] that is seen in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Lcn2, BAT cannot be fully activated by thermogenic (cold) stimulation and displayed low levels of thermogenic activity. A recent report by Paton et al (46) provides another line of evidence supporting that Lcn2 plays a positive role in mitochondrial oxidation function. In their study, recombinant Lcn2 promotes oleate oxidation in 3T3-L1 adipocytes; injection of Lcn2 increases energy expenditure in regular chow diet-fed mice.…”
Section: Lcn2mentioning
confidence: 92%